2017
DOI: 10.15740/has/au/12.techsear(6)2017/1612-1616
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of certain insecticides against diamondback moth (Plutella xylostellaL.) on cabbage (Brassica oleracea Var. Capitata L.)

Abstract: SUMMARY :Diamondback moth (Plutella xylostella L.) the most important destructive pest on cruciferous plants including of cabbage (Brassica oleracea var. capitata L.) through chemical control is effective against diamondback moth, development of resistance to insecticides often necessitates continuous evaluation and new molecules to manage the pest keeping in this view, the present study was conducted to evaluate the efficacy of seven insecticides against the incidence of diamondback moth in cabbage cultivar U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 5 publications
2
5
1
Order By: Relevance
“…Dalave et al [11] reported that the infestation of the pest was started from third week of December and thereafter population was gradually increased to attain a peak (8.9 larvae per plant) during fourth week January. However, present research find is in contrast with earlier finding by Aiswarya et al [12], Venugopal et al [13] and Lal et al [9], reported the highest peak of the population of diamondback moth during the month of February and March.…”
Section: Population Dynamics Of Diamondback Moth (Plutella Xylostella L) Infesting Cabbagecontrasting
confidence: 99%
See 1 more Smart Citation
“…Dalave et al [11] reported that the infestation of the pest was started from third week of December and thereafter population was gradually increased to attain a peak (8.9 larvae per plant) during fourth week January. However, present research find is in contrast with earlier finding by Aiswarya et al [12], Venugopal et al [13] and Lal et al [9], reported the highest peak of the population of diamondback moth during the month of February and March.…”
Section: Population Dynamics Of Diamondback Moth (Plutella Xylostella L) Infesting Cabbagecontrasting
confidence: 99%
“…Also, the population was negatively correlated with wind speed (r = -0.48) and rainfall (r = -0.38). The finding of present study in line with the finding of Venugopal et al, [13], reported positive correlation between minimum, maximum and average temperature and population of the pest. It is evident from present study that the infestation was initiated in last week of November and peak population of pest was noticed in the month of January.…”
Section: Population Dynamics Of Diamondback Moth (Plutella Xylostella L) Infesting Cabbagesupporting
confidence: 93%
“…The overall efficacy of the post treatment observations recorded at 3 and 7 DAT of two sprays (Figure 1) showed that spinosad 45 SC, indoxacarb 14.5 SC and emamectin benzoate 5% SG were found to be the best and the most effective being on par with 84.85, 77.40 and 69.17% reduction in population over untreated control and were significantly superior to all other treatments. A voluminous research data to confirm the results of spinosad is available (Dey and Somchoudhury, 2001, Mahalakshmi et al, 2002, Prithwiraj and Chatterjee, 2003, Tambe and Mote, 2003, Syed et al, 2004, Walunj and Pawar, 2004, Wemin and Wesis, 2006, Jasmine et al, 2007, Kumar et al, 2007c, Sable et al, 2007, Meena and Singh, 2013, Vaseem et al, 2014, Stanikzi and Thakur, 2016, Reddy et al, 2017, Sharma et al, 2017a, Venugopal et al, 2017and Yadav et al, 2017. Treatments…”
Section: Overall Mean Efficacy Of Both Spraysmentioning
confidence: 99%
“…It is also believed to be originated in South Africa based on the massive number of Brassica plants and parasitoids present (Kfir, 1998). Now, the diamondback moths are present worldwide and are reported in more than 128 countries (Venugopal et al, 2017). The widespread of DBM is due to its migrating capabilities.…”
Section: Population Ecology Of Diamondback Moth Plutella Xylostellamentioning
confidence: 99%
“…P. xylostella is the globally significant destructive pest attacking Brassicaceae crops (Venugopal et al, 2017). The pest's common control is still the frequent use of insecticides despite the resistance shown.…”
Section: Management Of Diamondback Mothmentioning
confidence: 99%